Building Character in Sufism-Based Students in Madrasah West Kalimantan - Sahri Sahri; Ali Usman Hali (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2023)
This article discusses building the character of Sufism-based students in Madrasah in West Kalimantan. The research used is qualitative research through a descriptive approach to understand the object of research naturally. Descriptive analysis is an analysis that uses narratives related to data found at the research site in explaining the intentions, content, and results of the study. The steps of this study are Data collection, Data Reduction, Data Analysis, and Conclusion. The results of this study show that in building the character of Sufism-based students, it aims to influence thoughts and deeds that are following Islamic values. In building the character of students in Madrasah in West Kalimantan, Sufism-based consists of several values, namely: 1) religious; 2) tolerance; 3) social care; 4) friendly; 5) nationalism; 6) cooperation; 7) honesty.